The Sawdust And Recycled Paper Potential As The Alternative Eco Construction Material For Product Design - Thuluganam, Thenmoli (2020)
The study was conducted to develop a method of creating bio composite strips based on sawdust and waste recycled paper, as the potential constructive eco-material product. In Malaysia, solid waste management has become a challenging task to accomplish in recent years due to economic development and population growth. Appropriate dumping sites are becoming increasingly difficult to obtain and most of the existing ones are nearly exhausted. Moreover, in Penang, wood excesses including sawdust are produced annually and these are usually not put into profitable use. Studies are being directed at the search for possible effective ways of utilising sawdust as well as conceivable ways of recycling paper materials.